2013
DOI: 10.1186/1477-7819-11-176
|View full text |Cite
|
Sign up to set email alerts
|

A case report of de novo hepatocellular carcinoma after living donor liver transplantation

Abstract: Post-transplant malignancy is the major cause of later death of recipients after liver transplantation. Tumor recurrence after liver transplantation for patients with hepatocellular carcinoma in the end stage of cirrhosis has been frequently encountered. However, de novo hepatocellular carcinoma originating from the liver allograft has only rarely been reported. Here we reported a case of de novo hepatocellular carcinoma developed 2 years after living donor liver transplantation for hepatitis B-related liver c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…On imaging it shows characteristic arterial phase enhancement with washout in venous phase and delayed capsular enhancement. De novo HCC is rarely encountered and chronic HCV and HBV infection remains a high risk factor for the development of HCC (10).…”
Section: Discussionmentioning
confidence: 99%
“…On imaging it shows characteristic arterial phase enhancement with washout in venous phase and delayed capsular enhancement. De novo HCC is rarely encountered and chronic HCV and HBV infection remains a high risk factor for the development of HCC (10).…”
Section: Discussionmentioning
confidence: 99%
“…Although current treatment guidelines for De-novo HCC after LT have not been well established, it was suggested that these cases be approached according to the current guidelines for primary and recurrent HCC[ 17 ]. The strategies that have been used in the reported cases to date are: re-transplantation ( n = 6)[ 4 , 6 - 9 , 14 ], trans-arterial chemoembolization (TACE) ( n = 4)[ 11 , 13 - 15 ], hepatic resection ( n = 3)[ 7 , 12 ], radiofrequecy ablation (RFA) ( n = 3)[ 10 , 11 , 14 ], medical therapy with Sorafenib ( n = 2)[ 13 , 14 ] and PMWA in our case. Two of the reported cases used more than one procedure[ 7 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, few cases of de novo HCC in LDLT have been reported. 6,7 Hence, the characteristics, probability of, and risk factors for de novo HCC remain poorly understood. In this study, we defined the donor origin of graft HCC using microsatellite analysis and elucidated the characteristics of de novo HCC from a database containing 2779 LDLT adult cases from nine major LT institutes in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Published studies on the development of de novo HCC in the graft post‐transplant are restricted by the limited number of case reports. In particular, few cases of de novo HCC in LDLT have been reported 6,7 . Hence, the characteristics, probability of, and risk factors for de novo HCC remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%